The Impact of COVID-19 on the Mental Health of Foreign Students Stranded from Chinese Universities - Abbas, Safdar; Tan, Qinyi; Safdar, Aamna; Teng, Luyan (Quality in Sport, 2022)
The study aims to inspect the influence of the pandemic of COVID-19 on the mental health of both undergraduate and postgraduate students, who have been stranded from Chinese universities. The study used the online questionnaire, which was comprised of three scales. These are self-rating anxiety scale (SAS), the self-rating depression scale (SDS), and the scale for social avoidance and distress (SAD). A total of 159 undergraduates and 153 postgraduate students have participated in this study and it comprises both males and females. For exploring the impact of the Covid-19 on the mental health of the students, who have been stranded from Chinese universities, the study has made the use of the independent sample t-test and analysis of variance (one-way ANOVA). The findings show that Mental health of students stranded from universities negatively affected due to high level of anxiety, depression, and social anxiety due to pandemic. However, the level of anxiety, depression, and social anxiety has reduced to some extent as compare to earlier studies after the emergence of pandemic of COVID-19. The outbreak of COVID-19 has affected females more than males and the postgraduate students have a lower level of depression as compared to the undergraduate students because they have shown a higher level of mean and standard deviation values. Moreover, the depression level was high among the students of Natural and Applied sciences. The results also confirm that the level of anxiety, depression, and social anxiety was high in the young students as compared to the mature ones. Then, the level of anxiety and social anxiety was high in the students, who could not resume their classes and degrees. The findings of this study suggest that the mental health o undergraduate and postgraduate students should be carefully monitored after the pandemic of COVID-19 because it has left a deep mark on their mental health. Furthermore, it also calls for proper psychological counseling for addressing the issues of depression and anxiety in them.